2012
DOI: 10.3109/03009734.2012.654861
|View full text |Cite
|
Sign up to set email alerts
|

Localized AL amyloidosis: A suicidal neoplasm?

Abstract: Although AL amyloidosis usually is a systemic disease, strictly localized AL deposits are not exceptionally rare. Such case reports form a considerable body of published articles. Although both AL amyloidosis types are formed from an N-terminal segment of a monoclonal immunoglobulin light chain, a typical localized AL amyloid differs from the systemic counterpart by the morphological appearance of the amyloid, and presence of clonal plasma cells and of giant cells. In this article it is pointed out that locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 66 publications
2
108
0
8
Order By: Relevance
“…Localized amyloidosis (''amyloidoma'') involves more frequently single districts (such as larynx, ureter, skin, eyelid, and cardiac atria) and is characterized by the occurrence of foci of monoclonal plasma cells that synthesize amyloidogenic light chains. It is conceivable that giant cells are able to misfold these chains to AL amyloid fibrils [81]. Systemic amyloidosis, on the other hand, is structurally heterogeneous and includes three main types:…”
Section: Localized and Systemic Amyloidosismentioning
confidence: 99%
“…Localized amyloidosis (''amyloidoma'') involves more frequently single districts (such as larynx, ureter, skin, eyelid, and cardiac atria) and is characterized by the occurrence of foci of monoclonal plasma cells that synthesize amyloidogenic light chains. It is conceivable that giant cells are able to misfold these chains to AL amyloid fibrils [81]. Systemic amyloidosis, on the other hand, is structurally heterogeneous and includes three main types:…”
Section: Localized and Systemic Amyloidosismentioning
confidence: 99%
“…It has been proposed that the pathogenesis of localised AL amyloidosis may differ from that of the systemic type, as suggested by the fact that in localised amyloidosis κ light chains are more frequent than the λ form, in contrast to the systemic form, where λ chains constitute the overwhelming majority of cases. It is suggested that oligomeric assemblies of the produced immunoglobulin light chain are toxic to plasma cells [33]. Light chains that compose amyloid deposits are the same as those expressed by the lymphoma cells.…”
Section: Nodular Pulmonary Amyloidosismentioning
confidence: 99%
“…Localized amyloidosis is typically seen in mucosal surfaces, such as the gastrointestinal tract (GIT), urinary tract, breasts, lungs and upper airways, as well as the skin [49]. It probably stems from a localized production of monoclonal LCs, and is thought to involve local amyloid phagocytic processing which provides the amyloidogenic properties of the LCs [50]. A diagnosis of localized AL amyloidosis is usually made after tissue sampling for symptoms induced by local deposition, although an incidental diagnosis can also occur.…”
Section: Diagnosismentioning
confidence: 99%